Estudio de factibilidad para la implementación de una aplicación web para la reservación de consultas médicas en el Centro de Salud Pueblo Nuevo - Saa Padilla, Sinty Marianela (2018)
The present project consists in carrying out a Feasibility study for the implementation of a web application for the reservation of medical consultations in the Pueblo Nuevo Health Center, which is a sub-line of research on the development of computer systems. Throughout the evolution of technology has been able to create new things for the benefit of society, in terms of the different applications that facilitate the administration of specific tasks from this point of view was achieved to observe the need to conduct a study for the proper use and management of reservations for medical consultations, through a web application at the Pueblo Nuevo Health Center. However, it has been observed that patients do not have the use of a technological tool that allows them to facilitate the reservations of medical consultations through a web application or by telephone, therefore, people have to go to the center. health to make a medical reservation and on all some patients do not have much time for work or for any personal situation, to take the time to book an appointment to the health center, wasting a lot of your time. It should be mentioned on the other hand that the administrator of the institution's consultations does it manually and in this way the records of the consultations tend to be lost. This problem depends on not having a good organization or an adequate system for the organization of medical consultations. Therefore, patients and officials of the Pueblo Nuevo Health Center will be beneficiaries through this web application, which may be reserved easily his medical consultations, and at the same time the officials will have the facility of obtaining their work schedules to the diary and the number of appointments to attend to the day, since it improves the control of acquired appointments.